What Every Girl Should Know - Bull, David (Element Children's Inc, 1999)
Finally, the ultimate in total girl's health! Feeling your best means not only having a healthy body, but a healthy mind, too! From Allergies to Zits (with stops in between at Periods and Self-image), What Every Girl Should Know gives the real low-down on the health issues that matter to today's pre-teen girls. Up-front and easy-to-use, this helpful A to Z guide also covers such important topics as Exercise, Nutrition, Personal care, Sleep and Stress. Plus, there's quizzes girls can take to find out how much they know about their own selves! What Every Girl Should Know -- every girl's guide to feeling good inside and out!
Keywords: General; Health & Daily Living; Juvenile Nonfiction